Assessing thromboembolic disease burden, risk perception, management, and management outcomes in Ghana - Wilson Bright Nyansah, George Asumeng Koffuor, Lorraine Sallah, Richmond Arthur (Journal of Applied Pharmaceutical Science, 2021)
Despite the widely documented and economic burden of thromboembolic disease (TED) globally, data on the true impact of the disease in Ghana are scanty. This study, therefore, aimed to assess TED burden, risk perception, and thromboprophylactic practices across general medical, surgery, and obstetrics and gynecology specializations in Ghana. A quantitative cross-sectional study was conducted in tertiary regional/district, polyclinic, and private hospitals in the Kumasi Metropolis of the Ashanti region of Ghana. The study indicated that TED was classified as medium risk in most areas of clinical practice and mostly reported in inpatient settings. Deep vein thrombosis and ischemic stroke were the most commonly reported diseases, with pain being the most common symptom. The practice of thromboprophylaxis was averagely practiced in most areas of clinical practice. Pharmacological management of TED was preferred with low-molecular-weight heparins and warfarin being the most widely used therapeutic options. The cost was the greatest factor hindering therapy and choice of medication. Bleeding was the most common side effect observed with therapy. Although therapies for management and prophylaxis of TED are available and effective, it is still a burden and perceived as a risk in clinical practice and healthcare delivery in Ghana because of the high cost of therapy
Keywords: Deep vein thrombosis, arterial thromboembolic events, thrombo-prophylaxis, lowmolecular-weight-heparins, ischaemic stroke, warfarin.